The Role of Bacteria as Basis on Pelagic Food Webs in Ultraoligotrophic Northern Patagonian Lakes: a Mini Review - De los Rios-Escalante, Patricio; Де лос Ріос-Ескаланте, П. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
The northern Patagonian lakes are located in the South American Andes between 38—41° of Argentina and Chile. In their original stage, these lakes were described as ultraoligotrophic due the presence of perennial native forest that avoided the nutrients inputs from surrounding basin. The first studies described low phytoplankton abundances, but in recent studies, the presence of mixotrophic ciliates has been reported that may be a basis on trophic webs under the ultraoligotrophic status. They can graze on heterotrophic bacteria and nannoflagellates and can also do photosynthesis. Under the ultraoligotrophic status, the bacteria would have the basis on pelagial food webs because these would be grazed by zooplankton and mixotrophic ciliates. Nevertheless, when the lakes have a transition from oligotrophy to mesotrophy, although the bacterial biomass increases, they would not have an exclusive role because of a complex interaction between phytoplankton and grazer zooplankton.